Female-owned innovative startups in Italy: Status quo and implications - Paola Paoloni; Giuseppe Modaffari (Administrative Sciences, 2018)
The aim of the paper is to provide an overview of the current literature of this business phenomenon with regard to gender studies and to point out what is substantially happening and what has happened in the Italian economic context. The main research questions were RQ1: How is the phenomenon of female Startups treated from a scientific point of view? RQ2: Which is the Italian situation of this phenomenon? The methodology used is both qualitative and explorative. A bidirectional analysis has been carried out for this purpose. In order to expand the first research question (RQ1), an analysis was carried out of the articles in the EBSCO database on the topic of female startups. In order to expand the second question (RQ2), an analysis was carried out on the data concerning the phenomenon of female startups, using the register of companies held at the Chambers of Commerce which were territorially competent. Our research, carried out within the Italian economic context, demonstrates how the phenomenon of Woman Startups (WSU), even if it is widely expanding, is inherent in all the typical elements of female entrepreneurship, as reported in the literature by gender scholars. The main factors that emerge for the WSU are the small size and the undercapitalization in the startup phase. This work contributes to the expansion of studies on the topic of startups in the context of gender and can be useful to the social context, new entrepreneurs, and practitioners of the sector.
Keywords: 350; startups; woman startups; gender analysis